Crystal Structure of Penicillin-Binding Protein 3 (PBP3) from Escherichia coli - Sauvage, Eric (Public Library of Science, 2014)

(untitled)
In Escherichia coli, penicillin-binding protein 3 (PBP3), also known as FtsI, is a central component of the divisome, catalyzing cross-linking of the cell wall peptidoglycan during cell division. PBP3 is mainly periplasmic, with a 23 residues cytoplasmic tail and a single transmembrane helix. We have solved the crystal structure of a soluble form of PBP3 (PBP3(57–577)) at 2.5 Å revealing the two modules of high molecular weight class B PBPs, a carboxy terminal module exhibiting transpeptidase activity and an amino terminal module of unknown function. To gain additional insight, the PBP3 Val88-Ser165 subdomain (PBP3(88–165)), for which the electron density is poorly defined in the PBP3 crystal, was produced and its structure solved by SAD phasing at 2.1 Å. The structure shows a three dimensional domain swapping with a β-strand of one molecule inserted between two strands of the paired molecule, suggesting a possible role in PBP3(57–577) dimerization.